Students' Responses in the Use of Quiziz Paper Mode in the Formative Evaluation of Qur'an Hadith Learning - Muhammad Saleh; Muzdalifah Muhammadun; Usman; Abdul Halik; Hasmaini (Al-Iftah: Journal of Islamic studies and society, 2025)
This study aims to analyze the ability of teachers to prepare test instruments using Quizizz in the formative evaluation of Qur’an Hadith learning at MTs DDI Taqwa, as well as to examine the effectiveness of its implementation and students’ responses toward it. Employing a qualitative descriptive approach, this research was conducted through field observations and in-depth interviews with Islamic Education (PAI) teachers at MTs DDI Taqwa, Parepare City. The qualitative paradigm used seeks to understand comprehensively the teacher’s performance and students’ experiences in applying Quizizz Paper Mode within the formative evaluation process.The findings reveal that teachers demonstrated a good level of competence in preparing test instruments using Quizizz Paper Mode. They were able to design items aligned with the Qur’an Hadith curriculum, considering question difficulty, and integrating cognitive aspects in accordance with learning objectives. The implementation of Quizizz in paper format presents an innovative alternative in assessment, especially in schools with limited access to digital technology. Despite the paper-based format, this method successfully preserves fairness, maintains engagement, and adapts the advantages of digital quizzes into a traditional testing environment. Moreover, students’ responses toward formative evaluations using Quizizz Paper Mode were highly positive. They expressed enthusiasm, found the tests more engaging, and showed greater confidence during evaluations. The use of this method also stimulated active learning, enhanced motivation, and created a more enjoyable and interactive learning atmosphere. Overall, the study concludes that Quizizz Paper Mode serves as a practical and effective solution in formative assessments for Qur’an Hadith learning, bridging innovation with contextual educational needs while fostering both teacher creativity and student participation.